PENGARUH PEMILU SERENTAK TERHADAP PARTISIPASI PEMILIH DALAM IMPLEMENTASI UNDANG-UNDANG NOMOR 7 TAHUN 2017 DI KABUPATEN BADUNG - I Ketut Arka (Majalah Ilmiah Widyacakra, 2020)
AbstractThis research aims to determine and analyze the level of participation voters, the impact of thesimultaneous elections and the barriers faced by the organizers at election 2019 in BadungRegency. The research method used is a qualitative descriptive research method. The datacollection techniques used are by observation, interviews and documentation. Once collecteddata is implemented data analysis that includes data reduction, data presentation and dataverification. Based on the data and analysis results that have been done is known that after thesimultaneous selection is carried out the participation rate increase is quite significant andobtained that the selection of legislatif is always in demand by voters it can be seen from thelevel of voters participation in the implementation of legislative elections is always higher thanthe election of other elections and regional head elections, the impact caused by Concurrentelections is the presence of victims who died from fatigue in the process of voting until thecounting of votes that require a very long time, on the other hand in accordance with theregulation of the voting implementation and the calculation of vote must be done on the sameday. elections budget can save the usability because several phases are lined up as well.